FINANCIAL SECURITY OF LOCAL BUDGETS: CHALLENGES AND PROSPECTS FOR SUSTAINABLE REGIONAL DEVELOPMENT (International Congress on Economics, Management and Business Studies, 2026)
This article extensively analyzes the issues of financial security of local budgets: challenges and prospects for sustainable regional development. It also extensively studies advanced foreign experience in ensuring the financial security of local budgets.
Keywords: Local budget, financial security, fiscal sustainability, local government, budget revenues, fiscal decentralization, regional development.